Age-related changes in time perception: Effects of immersive virtual reality and spatial location of stimuli - Bogon, Johanna; Jagorska, Cindy; Steinecker, Isa; Riemer, Martin (Acta psychologica, 2024)
The perception of time is subject to various environmental influences and exhibits changes across the lifespan. Studies on time perception have often been conducted using abstract stimuli and artificial scenarios, and recent claims for more naturalistic paradigms and realistic stimuli pose the question as to whether immersive virtual reality set-ups differently affect the timing abilities of older versus younger adults. Here, we tested the hypotheses that naturalistic 3D stimuli presented in immersive virtual reality (as opposed to abstract 2D stimuli presented on a computer screen) and the spatial location of those stimuli (left vs. right) affect the perceived time point of their occurrence. Our results demonstrate that a naturalistic presentation of stimuli leads to a bias towards earlier time points in younger, but not older participants. Furthermore, this bias was associated with lower scores of memory capacity. Contrary to our hypothesis that right-sided stimuli are perceived as later than left-sided stimuli, no spatial influences on temporal processing were observed. These results show that older and younger adults are differently affected by an increase in the realism and the immersiveness of experimental paradigms, and highlight the importance of task design in studies on human time perception.